DEVELOPMENT OF THE INDONESIAN TANGIBLE HERITAGE WEB EQUIPPED WITH VIRTUAL REALITY TO STRENGTHEN THE CULTURAL INSIGHTS OF SIJB STUDENTS, MALAYSIA - Bachri, Syamsul; Sapto, Ari; Kurnia Putra, Alfyananda; Kristanti, Yohana Ayu (LP2M STP Mataram, 2024)
This research contains a study of efforts to strengthen the cultural insights of Indonesian Johor Bahru School (SIJB) students, Malaysia through virtual reality-based learning media for cultural heritage. The focus of this research is to develop Web Indonesian Tangible Heritage learning media equipped with virtual reality technology. The development method used is ADDIE, consisting of 5 stages, namely: 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The study was conducted on 91 junior high school (SMP) students at SIJB, Malaysia. The results of the study show that the Web Indonesian Tangible Heritage learning media equipped with virtual reality technology has functionality that can work well, is able to strengthen cultural insights according to the target, and gets a positive response from users. Most students agree that learning integrated with technology can increase motivation in learning and improve understanding of the material.